Preimplantation Genetic Testing for a Chinese Family With X-Linked Lymphoproliferative Syndrome Type 1 - Chen, Songchang; Shi, Weihui; Qian, Yeqing; Wang, Liya; Zhang, Junyu; Li, Shuyuan; Chen, Yiyao; Chang, Chunxin; Fei, Hongjun; Zhang, Lanlan; Huang, Hefeng; Xu, Chenming (Frontiers in Genetics, 2020)
Background X-linked lymphoproliferative disease (XLP) is a rare primary immunodeficiency disorder. We performed experiments based on two strategies of preimplantation genetic testing (PGT) for a family with XLP caused by a mutation in SH2D1A (c.191G > A). Methods First, a single-cell polymerase chain reaction (PCR) protocol was established using single lymphocytes. A nested PCR experiment was performed with direct sequencing after whole genome amplification of single cells to assess the accuracy of the genetic diagnosis. Embryos obtained after intracytoplasmic sperm injection were biopsied on day 3 and detected using the established single-cell PCR protocol. In the second PGT cycle, targeted next generation sequencing (NGS) was performed and the single nucleotide polymorphism (SNP) markers flanking SH2D1A were selected to determine the disease-carrying haplotype phase in each embryo. Result In the first PGT cycle, six embryos were biopsied. Discounting an embryo from a single failed PCR experiment, five embryos were identified, including three unaffected and two hemizygous. After PCR, one normal embryo was transferred when it was developing into an early blastocyst. Although the ultrasound images indicated a viable singleton pregnancy, the implantation was on the cesarean scar. Therefore, an artificial abortion was performed. In the haplotyping cycle, six embryos were identified to have inherited a haplotype without pathogenic mutations. After the embryo implantation process failed twice, a successful singleton pregnancy was established, and subsequently, a healthy female child was born. Conclusion Targeted NGS with haplotyping analysis circumvents the laborious process of multiplex PCR and is more likely to ensure diagnostic accuracy. However, when a genetic recombination occurs close to the site of mutation, confirmed identification using selected SNP markers can be challenging.